Revisited role of the placenta in bile acid homeostasis - Ontsouka, Edgar; Schroeder, Mariana; Albrecht, Christiane (Frontiers in Physiology, 2023)
To date, the discussion concerning bile acids (BAs) during gestation is almost exclusively linked to pregnancy complications such as intrahepatic cholestasis of pregnancy (ICP) when maternal serum BA levels reach very high concentrations (>100µM). Generally, the placenta is believed to serve as a protective barrier avoiding exposure of the growing fetus to excessive amounts of maternal BAs that might cause detrimental effects (e.g., intrauterine growth restriction and/or increased vulnerability to metabolic diseases). However, little is known about the precise role of the placenta in BA biosynthesis, transport, and metabolism in healthy pregnancies when serum BAs are at physiological levels (i.e., low maternal and high fetal BA concentrations). It is well known that primary BAs are synthesized from cholesterol in the liver and are later modified to secondary BA species by colonic bacteria. Besides the liver, BA synthesis in extrahepatic sites such as the brain elicits neuroprotective actions through inhibition of apoptosis as well as oxidative and endoplasmic reticulum stress. Even though historically BAs were thought to be only "detergent molecules" required for intestinal absorption of dietary fats, they are nowadays acknowledged as full signaling molecules. They modulate a myriad of signaling pathways with functional consequences on essential processes such as gluconeogenesis -one of the principal energy sources of the fetus-and cellular proliferation. The current manuscript discusses the potential multipotent roles of physiologically circulating BAs on developmental processes during gestation and provides a novel perspective in terms of the importance of the placenta as a previously unknown source of BAs. Since the principle "not too much, not too little" applicable to other signaling molecules may be also true for BAs, the risks associated with fetal exposure to excessive levels of BAs are discussed.